Beyond liquidity: financial flexibility, operational efficiency and dynamics on firm value during economic shocks - Yanti Budiasih (Manajemen dan Bisnis, 2026)
Recent global economic disruptions have increased uncertainty in capital markets and challenged firms in maintaining firm value. In such conditions, firms require both financial resilience and operational capability to sustain competitiveness and market confidence. This study aims to examine the influence of financial flexibility, leverage, and operational efficiency on firm value and to explore how these mechanisms operate across different economic phases. The study uses panel data from manufacturing firms listed on the Indonesia Stock Exchange during the period 2020–2025. The findings indicate that financial flexibility and operational efficiency positively influence firm value, while leverage negatively affects firm value. The results further show that financial flexibility plays a stronger role during crisis periods by helping firms maintain liquidity and financial stability. In contrast, operational efficiency becomes more important during recovery periods as firms focus on improving productivity and competitiveness. In addition, operational efficiency partially mediates the relationship between financial flexibility and firm value. These findings highlight the complementary role of financial and operational capabilities in sustaining firm value under economic shocks.